Banalitas Iman di Era Digital: Telaah Pemikiran Søren Kierkegaard: The Banality of Faith in the Digital Age: An Examination of Søren Kierkegaard's Thought - Anggoro, Blasius Diki; Wijanarko, Robertus (Jurnal Filsafat Indonesia, 2025)
This study examines the influence of the crowd on the authenticity of faith through Søren Kierkegaard’s philosophy, particularly in the context of modern digital culture and technological advancements. In this era, popular culture and social media have blurred individual identity, fostering banality of faith—a shallow religiosity devoid of personal meaning. This research employs a qualitative method through library research, including a critical analysis of Kierkegaard's works and contemporary social phenomena. The focus is on how crowds push individuals to adopt majority views without deep reflection, undermining personal commitment to faith. Social media exacerbates this condition through algorithms that amplify collective trends, further trapping individuals in superficial religious formalities. Kierkegaard asserts that authentic faith requires personal commitment, deep reflection, and the courage to break away from the crowd's influence. The consequences of faith often demand suffering as a form of responsibility for life choices. Findings reveal that crowds and digital culture significantly contribute to the banality of faith, causing individuals to lose existential desire and the freedom to cultivate an authentic relationship with God. Kierkegaard's insights remain highly relevant, offering guidance toward authentic and personal faith amidst the challenges of modernity.